Towards a structural efficiency classification system. (August 2020) - Mena, Quisco
Abstract: This paper presents an objective methodology to assess material overuse through the determination of a  Structural Efficiency  parameter for building structures, and to demonstrate the feasibility of such measurement while providing preliminary results to support its importance. Despite the current scenario of climate emergency, building structures are evolving towards more material-demanding systems while designers, industry and the general public remain unaware of the related resource and energy waste. This may be, in part, because of the lack of an absolute, unified, consistent and objective way to assess material usage in building structures. The proposed methodology can be consistently applied across all materials, layouts and building uses, providing absolute measurements while considering the project-specific features. The initial results obtained show how floor typologies have evolved towards less efficient solutions driven by labour costs and the quest for thinner floors and longer spans. They also indicate that current buildings are consuming at least 16 to 80 times more structural material (equivalent to efficiencies between 6.25% and 1.25%) than the minimum theoretically required. Theoretical models do not follow the same parameters as the real designs, thus 100% efficiency is not necessarily the final goal; realistic targets could be those obtained from the energy sector and, once the efficiency measurement becomes mainstream, improvements from current average 4% efficiency to around 25% should be achievable within 20 years. In near-optimal solutions, structural requirements are sensitive to the building layout but less sensitive to site conditions (wind, snow, ground conditions, etc.). Self-weight is small compared to typical existing systems hence it becomes secondary. Selecting materials with a low working strain is key in highly efficient floor systems, to avoid over-sizing for serviceability. Considering the global importance of building structures' material consumption and embodied carbon, the construction industry must start measuring Structural Efficiency to systematically appraise the current material overspend and the potential savings, while investing in R&D of new structural systems driven by material efficiency, incorporating the latest technologies in automation and digital manufacturing. Material research should shift towards lower working strains instead of focusing on material strength.